The Secrets of the Conclaves : the Cardinals' intrigues and the power of the holy spirit : revealed by Abbot Atto Melani, secret agent in the service of the Sun King at the papal elections /: the Cardinals' intrigues and the power of the holy spirit : revealed by Abbot Atto Melani, secret agent in the service of the Sun King at the papal elections. (2013) - Unknown
No abstract available